Criminal law, philosophy and public health practice / edited by A.M. Viens, John Coggon and Anthony S. Kessel. - Viens, A. M. (Adrian M.); Coggon, John, 1980-; Kessel, A. (Anthony) (Cambridge bioethics and law., 2013)
The goal of improving public health involves the use of different tools, with the law being one way to influence the activities of institutions and individuals. Of the regulatory mechanisms afforded by law to achieve this end, criminal law remains a perennial mechanism to delimit the scope of individual and group conduct. Utilising criminal law may promote or hinder public health goals, and its use raises a number of complex questions that merit exploration. This examination of the interface between criminal law and public health brings together international experts from a variety of disciplines, including law, criminology, public health, philosophy and health policy, in order to examine the theoretical and practical implications of using criminal law to improve public health.